Effects of flunarizine on experimental cerebral malaria (Colombia Medica, 1993)
To evaluate flunarizine effects as a selective blocker of calcium channels in cerebral malaria, flunarizine, an experimental model in Swiss mice infected with Plasmodium berghei var anka was developed, with forty age and weight standardized animals divided into four therapeutic groups: no treatment, flunarizine, chloroquine, and chloroquine-flunarizine. The neuropathological examination showed a statistically significant protective effect in the group with chloroquine-flunarizine treatment as compared to the group with chloroquine alone (Fischer test< 0.01). The elevated morbimortality of human cerebral malaria should justify the use of selective blockers of calcium channels in the central nervous system, like flunarizine, as an adjuvant to antimalarial treatment in clinically controlled trials.